Peningkatan Kemampuan Koneksi Matematis Melalui Computational Thinking Menggunakan Scartch di SMPN 4 Ciawigebang - Candra, Chairil; Mahpudin, Asep (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Mathematics learning at SMP Negeri 4 Ciawigebang generally still relies on textbooks and lecture methods, making the learning process monotonous and less interesting. This research aims to improve mathematical skills using Scratch media. The research method used was quantitative with a Quasi Experimental design, Pretest-Posttest Control Design, at SMP Negeri 4 Ciawigebang. The research population was students in grades 8b and 8e, totaling 54 students. Data was collected through observation, tests and questionnaires. The research results show that there is an increase in student learning outcomes after applying Scratch media to the material on two-variable linear equation systems.